Corporate social responsibility management based on Maqashid Al- Shariah - Fatin Fadhilah Hasib, A Syifaul Qulub, Ririn Tri Ratnasari, (Opción, 2019)
This research aims to describe Shariah-based corporate socialresponsibility management in accordance with Maqashid Al-Shariahprinciples as a new perspective on PT Petrokimia Gresik via qualitativeand phenomenological approach with two modes as recommended byBogdan and Biklen as an analysis technique. This study result showedthat programs carried out by PT Petrokimia Gresik are in tune withMaqashid Al-Shariah. In conclusion, BUMN management, especiallyPT Petrokimia Gresik is expected to be able to carry out CSRmanagement that provides great benefits to the community withprograms that are innovative and have a good impact on the company'sfuture